THE INSTITUTION OF RENUNCIATION OF INHERITANCE: HISTORY OF FORMATION AND DEVELOPMENT - M. Bychko; I. Komarevtseva (Гуманитарные и юридические исследования)
Recently, the Russian legal doctrine has begun to pay more attention to the study of the legal nature of the refusal of inheritance, but most studies are devoted to the analysis of the current state of the institute, including the consideration of the principles, methods, and procedure for the refusal of inheritance. The authors of the article believe that the study of historical and foreign experience in the formation of the institution of inheritance rejection is of great importance due to the fact that modern Russian legislation and practice in this area are not without shortcomings and gaps, they still need to be improved. Retrospective analysis contributes to a deeper and more comprehensive study, equips the researcher with new ideas and arguments. The article analyzes the features of the ancient Roman refusal of inheritance, and examines the fate of the national institute, starting from the period of Ancient Russia. The authors came to the conclusion that in Roman law, the relationship of refusal of inheritance was regulated in detail, and already at that time the prototype of the institution of directed refusal of inheritance began to form. The authors focused on the legal consolidation of the Institute of renunciation of inheritance in the draft Civil code of 1905, where the institute was called "renunciation of inheritance" by analogy with the Code of laws of the Russian Empire, and paid special attention to its development in the Soviet period. All codiied acts of civil legislation, starting with the civil code of the RSFSR in 1922, regulated relations on the rejection of inheritance. In the civil code of the RSFSR of 1964, for the irst time, the right to refuse inheritance was established for both the heir by law and the heir by will, but this right was limited to a period of six months from the date of opening the inheritance. The article presents the alternative experience of France and Germany, and demonstrates the commitment of modern Russian legislation to the main approaches of the civil code of the RSFSR of 1964, and the "adoption system" in many countries, including France.